2018
DOI: 10.14814/phy2.13868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic training on baseline expression of signaling and respiratory proteins in human skeletal muscle

Abstract: Most studies examining the molecular mechanisms underlying adaptation of human skeletal muscles to aerobic exercise focused on the response to acute exercise. Here, we examined the effect of a 2‐month aerobic training program on baseline parameters in human muscle. Ten untrained males performed a one‐legged knee extension exercise for 1 h with the same relative intensity before and after a 2‐month aerobic training program. Biopsy samples were taken from vastus lateralis muscle at rest before and after the 2 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 72 publications
0
14
0
1
Order By: Relevance
“…Changes in the protein content of human skeletal muscle after regular exercise (2 months of aerobic exercise training) were compared with changes in baseline transcriptome profiles and with contractile activity-specific transcriptome responses to acute exercise. Previously, we showed that this training program increased ADP-stimulated mitochondrial respiration in permeabilized muscle fibers, and endurance performance in an incremental one-legged knee extension exercise and an incremental cycling test 7,14 .…”
Section: Resultsmentioning
confidence: 90%
“…Changes in the protein content of human skeletal muscle after regular exercise (2 months of aerobic exercise training) were compared with changes in baseline transcriptome profiles and with contractile activity-specific transcriptome responses to acute exercise. Previously, we showed that this training program increased ADP-stimulated mitochondrial respiration in permeabilized muscle fibers, and endurance performance in an incremental one-legged knee extension exercise and an incremental cycling test 7,14 .…”
Section: Resultsmentioning
confidence: 90%
“…FOXO1 is an important regulator of ubiquitin-and autophagylysosomal-dependent proteolysis within skeletal muscle. In our previous paper (31), we showed that the long-term aerobic training increases baseline phosphorylation of FOXO1 Ser256 (a marker of deactivation of this transcription factor). The ubiquitin-proteasome system plays an important role in regulating biogenesis of mitochondria by ubiquitinating maturing mitochondrial proteins in the cell cytoplasm and in various mitochondrial compartments (2,22).…”
Section: Discussionmentioning
confidence: 88%
“…Mitochondrial biogenesis is an important adaptation to increase the oxidative capacity of the contracting muscle (Fritzen et al 2019 ; Holloszy 1967 ; Perry et al 2010 ), and requires a coordinated expression of nuclear genes encoding mitochondrial proteins and genes encoded in the mitochondrial genome (Holloszy 2008 ; Hood 2001 ). Transcription regulators (TFAM) and co-activators (PGC1-alpha) are important in regulating mitochondrial biogenesis and adaptation to endurance exercise (Olesen et al 2010 ), and have been shown to increase with 2–8 weeks of endurance training (Egan et al 2013 ; Popov et al 2018 ). Translational expression of TFAM protein content is associated with its transient increases in mRNA expression after each exercise bout (Popov et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%